Effect of drying on vitamin, carotene, organic acid, mineral composition, and microstructural properties of mango (Mangifera indica). Issue 2 (16th December 2021) - Sarkar, Tanmay; Salauddin, Molla; Sheikh, Hassan Ibrahim; Pati, Siddhartha; Chakraborty, Runu
Abstract: Mangoes are rich in vitamins, carotenes, organic acids (OA), and minerals. Sun, convective, microwave, and freeze‐drying have been adopted for mango leather processing. Raw mango pulp (RMP) was found superior in vitamin A (1.52 ± 0.06 mg/100 g) and ascorbic acid (41.58 ± 1.36 mg/100 g) content. Vitamin D was not detected in the raw or dried product. Citric acid is found highest in the RMP (633.70 ± 2.05 mg/100 g). Drying significantly affects the vitamin (decrement of 20.32%–92.69% for vitamin A, 16.58%–61.31% for tocopherols, 29.94%–143% for vitamin C), and carotene content (3.17%–87.99% decrease). An increase of 5.62% and 15.16% in propionic acid content was observed for microwave and sun‐dried products respectively, while a decrease of 6.48% to 9.98‐fold was there for other OA. Crystal formation was observed in all samples except microwave dried. Microwave drying was found the best method in terms of nutrient retention may be due to the requirement of a relatively shorter drying time. Novelty impact statement: Mango leather is a traditional snack product with high nutritional value. The in‐depth vitamins and mineral composition is studied in different processing methods along with its microstructural changes that may take place in different drying processes.